Development of heavyweight high performance fiber reinforced cementitious composites (HPFRCC) - Part I: Mechanical properties - Tufekci, M. Mansur; Gokce, Ahmet (ELSEVIER SCI LTD, 2017)
This paper addresses the development of heavyweight high performance fiber reinforced cementitious composites (HPFRCC) incorporating silica sand-quartz powder blend, granulated ferrous waste or barite as fine aggregate. In this phase of the experimental program, the effects of three types of aggregates on mechanical properties of HPFRCC were investigated. Additionally, three different water-to-binder ratios, and three different steel fiber volume fractions were the other experimental variables. Also two different curing conditions (standard water curing and steam curing) were applied to HPFRCC specimens. Particle shape and surface morphology of the aggregates were analysed by scanning electron microscopy (SEM). Compressive strength, flexural strength and flexural toughness of the HPFRCC series were examined and discussed with regard to fine aggregate characteristics. The results showed that the highest flexural strength was achieved in the series incorporating granulated ferrous waste. Furthermore, all test series exhibited a ductile response and deflection-hardening behavior, regardless of the aggregate type and volume fraction of steel fiber. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: High performance fiber reinforced; cementitious concrete (HPFRCC); Heavyweight aggregates; Granulated ferrous waste; Barite sand; Mechanical properties; DURABILITY PROPERTIES; FLEXURAL BEHAVIOR; CONCRETE; AGGREGATE; IRON; Construction & Building Technology; Engineering; Materials Science